Da essência da técnica ao pensamento meditativo: caminhos para a formação humana - Rodrigues, Raísla Girardi (2022)
Contemporary education shows development and modernization, especially in the technological field. On the other hand, it also demonstrates to be suffering a distance from the ideia of formation thought in the sense of Bildung. However, such a notion is necessary, in our view, to ensure a critical and plural educational project, which contemplates human beings with their most diverse interests and possibilities of achievement. Inserted in a mercantile context, education allows itself to be governed by the logic of business administration, where the subjects involved in this process tend to be understood as numbers and labor for the job market. It is no longer a matter of formation in the sense of improving rationality, cultivating the soul and promoting reflective thinking. The focus falls back on obtaining knowledge and practices capable of assisting in the production of resources relevant to the capitalist-neoliberal demand, which expands the reach of the technical forces that, in Heidegger's understanding, condition the modern world. These technical forces are not simply equivalent to the impact of the technological apparatuses that permeate our existence, rather, they refer to the fundamental posture that underlies everything technical. A posture that structures our relationship with the world in such a way that our understanding of being and ourselves is framed by the challenge of exploitation and ordination of the real. This thesis aims, therefore, through a bibliographical and hermeneutic perspective, to bring the educational field closer to the question concerning technology, developed by Martin Heidegger, exposing a diagnosis of the present time and possible paths for a possible formation within the limits of the technical world. We tried to elucidate that the greatest danger of the technique is due to the narrowing of thought and the openness of the world, which results in a reduced formation.We conclude that there is a possible formative dimension since heideggerian diagnosis of the domain of technique in the modern world. When we reach, through meditative thinking, the awareness of the essence of technology, we conquer some freedom in our relationship with it. Therefore, becoming aware of technology is the condition for formation in the sense of self-cultivation, whose main trait is the serene posture in the face of its demands. To form oneself in serenity is to learn how to say yes and to say no to technology: to learn to accept its irreversible presence and what potential it brings to life, but not allow oneself to be enframed by its homogenizing force. This preserves a stronghold for the singular, where difference and radical novelty can survive. In this sense, the special way of thinking that Heidegger calls meditation becomes central. To form oneself in a serene relationship with technology demands the cultivation of reflection, meditation about ourselves and our world to be capable of inaugurating new meanings, ensuring ways of life and formative processes different from those proposed by the technique.